Edukasi Pembuatan Teknologi Asap Cair Sebagai Pengendali Hama Wereng Pada Budidaya Padi - Iqbal Erdiansyah; Liliek Dwi Soelaksini; Berlina Yudha Pratiwi; Eliyatiningsih Eliyatiningsih; Ade Jutawan Yusuf Maulana; Ni Putu Eka Sari Febyanti (Journal of Community Development, 2024)
Rice is a staple food for most of the Indonesia's population, so various efforts to be made to maintain continuity of production. Jember Regency is one of the rice production centers in East Java Province with production numbers continuing to decline over the last few years. One of the reasons for this decline in rice production is the increase in planthopper pest attacks due to climate change. The Jaya Abadi farmer group is one of the farmer groups in the rice production center area which always cultivates rice commodities every year. Based on problem identification and discussions with partners, it is known that planthopper pest attacks are the main threat in rice cultivation, because they can cause puso or crop failure. Seeing these conditions, community service activities that will be carried out include socialization and training in making liquid smoke pesticides as an alternative for controlling planthopper pest attacks. The production of liquid smoke is carried out by utilizing agricultural waste, which is often found in the partners' surrounding environment. This agricultural waste will be processed into liquid smoke using simple pyrolysis technology. Liquid smoke contains several compounds that can be used as a pesticide to exterminate plant pests. Based on the activity evaluation, it is known that socializatio and training activities can increase farmers' knowledge and skills in controlling planthopper pests by using liquid smoke pesticides. Apart from being cheap and easy to make, using liquid smoke pesticides can also reduce costs and safe for the environment.